Identification of Airborne Flora Before and After Activities in the Libraryand Classrooms of the Faculty of Medicine, Yarsi University, and a Review From an Islamic Perspective - Maitsa Hasna Kamalah; Ike Irmawati Purbo Astuti; Titiek Djannatun (Jurnal Indonesia Sosial Sains, 2026)
Libraries and classrooms are indoor environments with high usage intensity, making Indoor Air Quality (IAQ) crucial for the health and comfort of occupants. Indoor air flora is influenced by various environmental factors, including human activities, occupant density, temperature, humidity, lighting, and ventilation. Airborne microorganisms can act as vectors for pathogens that impact health; therefore, monitoring air flora before and after activities is essential. This study employed a descriptive quantitative–qualitative approach. A total of 20 air samples were collected from the library and classrooms using the settle plate method with Nutrient Agar media, both before and after activities. Samples were incubated at 37°C for 24–48 hours, after which bacterial colonies were counted (CFU) and identified based on colony morphology and Gram staining. The results showed an increase in airborne colonies after activities, particularly in classrooms, with the highest count observed in Class 10A. The library exhibited relatively fewer colonies, remaining below the standard IAQ threshold of 700 CFU/m³. Microbial identification revealed that Gram-negative Cocci dominated in classrooms, while Gram-positive Cocci were more prevalent in the library. These results indicate that human activities contribute significantly to the increase in airborne microorganisms. In conclusion, high occupancy rates and activity levels in classrooms lead to higher microbial loads, whereas libraries maintain lower counts. Human activity directly affects the concentration of indoor air microorganisms. To support a healthy and comfortable learning environment, effective hygiene management and optimal ventilation systems are essential for maintaining good Indoor Air Quality.